Digital assessment of preliminary impression accuracy for edentulous jaws: Comparisons of 3-dimensional surfaces between study and working casts. Issue 3 (July 2016) - Matsuda, Takashi; Goto, Takaharu; Kurahashi, Kosuke; Kashiwabara, Toshiya; Watanabe, Megumi; Tomotake, Yoritoki; Nagao, Kan; Ichikawa, Tetsuo
Abstract: Purpose: The aim of this study was to compare 3-dimensional surfaces of study and working casts for edentulous jaws and to evaluate the accuracy of preliminary impressions with a view to the future application of digital dentistry for edentulous jaws. Methods: Forty edentulous volunteers were serially recruited. Nine dentists took preliminary and final impressions in a routine clinical work-up. The study and working casts were digitized using a dental 3-dimensional scanner. The two surface images were superimposed through a least-square algorithm using imaging software and compared qualitatively. Furthermore, the surface of each jaw was divided into 6 sections, and the difference between the 2 images was quantitatively evaluated. Results: Overall inspection showed that the difference around residual ridges was small and that around borders were large. The mean differences in the upper and lower jaws were 0.26 mm and 0.45 mm, respectively. The maximum values of the differences showed that the upward change mainly occurred in the anterior residual ridge, and the downward change mainly in the posterior border seal, and the labial and buccal vestibules, whereas every border of final impression was shortened in the lower jaw. The accuracy in all areas except the border, which forms the foundation, was estimated to be less than 0.25 mm. Conclusion: Using digital technology, we here showed the overall and sectional accuracy of the preliminary impression for edentulous jaws. In our clinic, preliminary impressions have been made using an alginate material while ensuring that the requisite impression area was covered.